2013
DOI: 10.1111/1744-7917.12028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of destruxins on free calcium and hydrogen ions in insect hemocytes

Abstract: Destruxins, cyclohexadepsipeptidic mycotoxins isolated from the entomopathogenic fungus Metarhizium anisopliae, inhibit innate insect immunity. However, their mechanism of action remains unclear. In this study, the effects of destruxins on changes in free calcium and hydrogen ions in the hemocytes of Exolontha serrulata, Bombyx mori and the Spodoptera litura SL-1 cell line were detected using laser scanning confocal microscopy (LSCM). An instant Ca(2+) influx of hemocytes induced by destruxins A and B (DA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…In BLI assays, the results indicated that the responses of BmArgRS and BmLamin-C proteins were positively correlated with DA concentrations. There were affinity constant (K D ) values of 5.53 × 10 −5 and 8.64 × 10 −5 M respectively for DA with BmArgRS and BmLamin-C (Table 1, Figure 1B). However, the results showed that BmLamin-C is not a DA-binding protein, because a significant correlation between DA concentration and response of BmPRP1 was not detected.…”
Section: Interactions Of Destruxin a With Three Proteins By Bli And Cmentioning
confidence: 99%
See 1 more Smart Citation
“…In BLI assays, the results indicated that the responses of BmArgRS and BmLamin-C proteins were positively correlated with DA concentrations. There were affinity constant (K D ) values of 5.53 × 10 −5 and 8.64 × 10 −5 M respectively for DA with BmArgRS and BmLamin-C (Table 1, Figure 1B). However, the results showed that BmLamin-C is not a DA-binding protein, because a significant correlation between DA concentration and response of BmPRP1 was not detected.…”
Section: Interactions Of Destruxin a With Three Proteins By Bli And Cmentioning
confidence: 99%
“…For this, it is necessary to elucidate the targets of DA acting on insects. In the past decade, several studies indicated that DA changes the morphology of hemocytes and brings on equilibrium chaos of intra-and extra-cellular hydrogen and calcium ion in Bombyx mori [4,5], and regulates immune related gene expression [6,7]. Recently, a few DA binding-proteins in silkworm were found [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of antimicrobial peptides was also reduced after Drosophila melanogaster were treated with DA (Pal et al., ). Destruxin also acts as a kind of calcium ionophore and an inhibitor of V‐H + ‐ATPase (Bandani et al., ; Chen et al., ). Other studies have reported that destruxins damage the organs and tissues of insects, including the midgut, Malpighian tubules, salivary glands, and muscle (Kershaw et al., ; Sowjanya Sree et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Destruxin A (DA), the common analogue of entomopathogenic fungus, Metarhizium anisopliae , has substantial insecticidal activity [ 1 , 2 , 3 ]. Research has shown that DA can destroy an insect’s innate immune system, which includes breaking the balance between calcium ion and hydrogen ion in hemocytes [ 4 ], affecting the function of phagocytosis and encapsulation in hemocytes [ 5 ] and inhibiting the biosynthesis of the antibacterial peptides in drosophila [ 6 ]. Our previous research suggests that, although relatively large doses of DA is required to kill the silkworm ( Bombyx mori ) Bm12 cell, smaller dosages are sufficient to cause morphological changes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%